Tethered Swimming Can Be Used to Evaluate Force Contribution for Short-Distance Swimming Performance - Morouço, Pedro (2020)
The purpose of this study was two-fold: (a) to compare stroke and the physiological responses between maximal tethered and free front crawl swimming and (b) to evaluate the contribution of force exertion for swimming performance over short distances. A total of 34 male swimmers, representing various levels of competitive performance, participated in this study. Each participant was tested in both a 30-second maximal tethered swimming test and a 50-m free swimming test. The tethered force parameters, the swimming speed, stroke (stroke rate [SR]), and the physiological responses (increase in blood lactate concentration [ΔBLa], heart rate, and rate of perceived exertion) were recorded and calculated. The results showed no differences in stroke and the physiological responses between tethered and free swimming, with a high level of agreement for the SR and ΔBLa. A strong correlation was obtained between the maximum impulse of force per stroke and the speed (r = 0.91; p < 0.001). Multiple regression analysis revealed that the maximum impulse and SR in the tethered condition explained 84% of the free swimming performance. The relationship between the swimming speed and maximum force tended to be nonlinear, whereas linear relationships were observed with the maximum impulse. This study demonstrates that tethered swimming does not significantly alter stroke and the physiological responses compared with free swimming, and that the maximum impulse per stroke should be used to evaluate the balance between force and the ability to effectively apply force during sprint swimming. Consequently, coaches can rely on tethered forces to identify strength deficits and improve swimming performance over short distances.